Katie Smith: capstone - Smith, Katie, artist (Colorado State University. Libraries, 2014)
The artist's statement: There are certain associations that people make with ceramic objects; the cup you drink your morning coffee out of, or the vase that you pull out when you are given flowers. These associations, and the forms that embody them act as my starting point from which I would like to see how drastically I can stretch the form while still maintaining function. I search for a form, which could function as a cup or a bowl or a vase but might not be recognized as those things at first impression. The objects cannot be approached as readily as you would approach a more familiar cup in your cupboard, but hopefully they require more playful, thoughtful interaction. The form of my pieces require a slower approach; the user is required to be aware of the form when deciding which side of the rim is best suited for a lip or which opening each stem of a bouquet should be put in, or which curve of the surface the food would sit best on. Comfort and ease of use come secondary to intrigue and meaningful interaction. This kind of playfulness and curiosity that exists when someone approaches and object that is familiar but still foreign to them, is an interest of mine that continues in my thinking about surface design. Color, pattern, symmetry, and asymmetry can be used to both simplify and complicate a form or a composition. I try to use pattern and color in a way that challenges what you expect. I want a surface to confuse the space that it is in or the form that it is on and allow the viewer to focus in or out moving back and forth between areas of pattern and form. I use pattern as a tool to flatten three-dimensional space as well as to provide dimension where there is none.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.